Digital twin-based resilience evaluation and intelligent strategies of smart urban water distribution networks for emergency management - Hongyan Dui; Taiyu Cao; Fan Wang (Resilient Cities and Structures)
Resilient smart urban water distribution networks are essential to ensure smooth urban operation and maintain daily water services. However, the dynamics and complexity of smart water distribution networks make its resilience study face many challenges. The introduction of digital twin technology provides an innovative solution for the resilience study of smart water distribution networks, which can more effectively support the network's real-time monitoring and intelligent control. This paper proposes a digital twin architecture of smart water distribution networks, laying the foundation for the resilience assessment of water distribution networks. Based on this, a performance evaluation model based on user satisfaction is proposed, which can more intuitively and effectively reflect the performance of urban water supply services. Meanwhile, we propose a method to quantify the importance of water distribution pipes' residual resilience, considering the time value to optimize the recovery sequence of failed pipes and develop targeted preventive maintenance strategies. Finally, to validate the effectiveness of the proposed method, this paper applies it to a water distribution network. The results show that the proposed method can significantly improve the resilience and enhance the overall resilience of smart urban water distribution networks.